Comparison of rate of canine retraction and anchorage potential between mini-implant and conventional molar anchorage: An In vivo study - D Davis; R Krishnaraj; Sangeetha Duraisamy; K Ravi; S Dilip; Anila Charles; N C Sushil (Wolters Kluwer Medknow Publications, 2018)
Aim: The aim of this study was to compare the rate of canine retraction, the anchorage loss, and the change in the inclination of the first molars between molar and mini-implant anchorage. Objective: (1) To compare the rate of canine retraction between conventional molar anchorage and mini-implant anchorage in the maxilla and mandible. (2) To compare the amount of anchor loss between mini-implant-anchored and molar-anchored sides during canine retraction in the maxilla and mandible. Materials and Methods: Ten patients were included in the study. The implants were loaded immediately by applying a force of 100 g. Measurements were made in the pre-retraction and post-retraction lateral cephalograms. A line drawn vertically from the sella-nasion plane through the distal pterygomaxillary point was used as a reference line. Results: The mean rates of canine retraction were 0.95 and 0.82 mm/month in maxilla on the implant and molar sides, respectively, and were 0.81 and 0.76 mm/month in mandible on the implant and molar sides, respectively. The mean anchorage loss was 0.1 mm on the implant side and 1.3 mm on the molar side of the maxilla and 0.06 mm on the implant side and 1.3 mm on the molar side of the mandible. The mean change in molar inclination was 0.3° on implant side and 2.45° on molar side of the maxilla and was 0.19° on implant side and 2.69° on molar side of the mandible. Conclusions: Implant anchorage is an efficient alternative to molar anchorage.